2010
DOI: 10.19142/rpq.v4i7.108
|View full text |Cite
|
Sign up to set email alerts
|

Decomposição dos Antirretrovirais Lamivudina e Zidovudina pelo Processo Fotofenton Assistido no Efluente de Indústria Farmoquímica

Abstract: Os princípios ativos utilizados na formulação de medicamentos compõem os contaminantes presentes na estação de tratamento de indústria farmacêutica. Visando alternativas que levem a soluções eficazes, os processos oxidativos avançados (POA) têm atraído grande interesse da comunidade científica e industrial. Foram realizadas degradações dos antirretrovirais (lamivudina -3TC e zidovudina -AZT), por oxidação, fotodegradação e foto-oxidação, presentes em efluentes de uma indústria farmoquímica do Estado de Goiás. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…Darunavir, lamivudine, and tenofovir have NOEC values below 10 mg/L, which are possible concentrations in a pharmaceutical effluent. Regarding concentration in industrial effluents, the work by Souza et al (2010) shows that the maximum concentrations of zidovudine and lamivudine, which are 6.29 mg/L and 3.22 mg/L respectively, do not come close to the NOECs for these substances.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Darunavir, lamivudine, and tenofovir have NOEC values below 10 mg/L, which are possible concentrations in a pharmaceutical effluent. Regarding concentration in industrial effluents, the work by Souza et al (2010) shows that the maximum concentrations of zidovudine and lamivudine, which are 6.29 mg/L and 3.22 mg/L respectively, do not come close to the NOECs for these substances.…”
Section: Resultsmentioning
confidence: 98%
“…High concentrations are expected in industrial effluent treatment plants. A study with real effluents from a zidovudine and lamivudine production plant found drug concentrations of 6.29 mg/L and 3.22 mg/L, respectively (Souza, et al, 2010). Therefore, even if a drug is classified as highly toxic and by the studies currently published, there is an indication that the values of environmental concentrations are low.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the photo-Fenton process, it managed to degrade the dye under study in the two radiations analyzed, especially with regard to the chromophore group (622 nm). In this AOP, ferrous ions act as electron donors for radical systems, while hydrogen peroxide decomposes into radicals and hydroxyl ions, causing the oxidation of ferrous ions to ferric ions(SOUZA et al 2010). Thus, the photo-Fenton/LED and photoperoxidation/UV-C systems went on to the optimization step of the variables [H2O2] and [Fe] (when applicable).…”
mentioning
confidence: 99%
“…A eficiência do processo Fenton depende de alguns parâmetros operacionais: pH, concentrações de H2O2, Fe 2+ e do contaminante, temperatura, composição da matriz (presença de ânions -carbonato/bicarbonato, fosfato, cloreto, sulfato, etc), fonte de radiação e espécie de ferro (SOUZA et al, 2010;BRITO e SILVA, 2012;TROVÓ et al, 2013).…”
Section: Parâmetros Operacionais Do Processo Foto-fentonunclassified